INFLUENCE OF EXOGENOUSLY APPLIED GLUTATHIONE AND GIBBERELLIC ACID IN A BEAN UNDER SALT STRESS IN VITRO CONDITIONS - Rasheed, Ruqia K.; Neamah, S. I. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2025)
This stady was aimed to investigate effect of treatment with 0, 0.25 and 0.50 mM of Glutathione (GSH) and 0, 1.0 and 2.0 mg L-1 of Gibberellic acid (GA3) in enhancing the growth of calli cultures was tested under normal and critical concentrations of sodium chloride (NaCl). The experiments were conducted during October, 2022 to June 2023 at the plant tissue culture laboratory in Center of Desert Studies, University of Anbar. The experiments designed according to the complete randomized design (CRD). The critical limit of NaCl in calli cultures was determined after 35 days of cultivation in MS medium. The results showed that the concentration of 200 mM caused the highest significant decrease in the fresh weight (FW) and relative fresh weight (RFW) of these cultures, which amounted to 457 mg and -0.086, respectively. However, it did not differ significantly with what was produced by the concentration with 150 mM. As for the salinity experiment, the combination of 0 mM + 0.5 mM + 2.0 mg L-1 for each of NaCl, GSH, and GA3, respectively, was the most consistent in improving the study indicators. This combination achieved the highest significant average for FW, dry weight (DW), RFW, and the effectiveness of Catalase (CAT) which amounted to 973.7 mg, 52.8 mg, 0.947, and 13.119 U mg-1 protein, respectively. However, the combination with the combination of 0 mM + 0.5 mM + 1.0 mg L-1 for each of NaCl, GSH and GA3, respectively, were recorded the lowest significant level of Malondialdehyde (MDA) content, which amounted to 1.951 µM g-1 FW.